2016
DOI: 10.1155/2016/1497213
|View full text |Cite
|
Sign up to set email alerts
|

Influencing Factors on the Overestimation of Self-Reported Physical Activity: A Cross-Sectional Analysis of Low Back Pain Patients and Healthy Controls

Abstract: Introduction. The aim of the present study was to determine the closeness of agreement between a self-reported and an objective measure of physical activity in low back pain patients and healthy controls. Beyond, influencing factors on overestimation were identified. Methods. 27 low back pain patients and 53 healthy controls wore an accelerometer (objective measure) for seven consecutive days and answered a questionnaire on physical activity (self-report) over the same period of time. Differences between self-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(60 citation statements)
references
References 34 publications
3
57
0
Order By: Relevance
“…We observed that LBP did not introduce bias in self-reported MVPA if the interaction between accelerometer-based MVPA and LBP was removed from the model. This is in line with previous research (11,31) on bias introduced by musculoskeletal pain. Thus, our results illustrate the limitation of statistical models used in previous studies of differential bias.…”
Section: Gupta Et Alsupporting
confidence: 93%
“…We observed that LBP did not introduce bias in self-reported MVPA if the interaction between accelerometer-based MVPA and LBP was removed from the model. This is in line with previous research (11,31) on bias introduced by musculoskeletal pain. Thus, our results illustrate the limitation of statistical models used in previous studies of differential bias.…”
Section: Gupta Et Alsupporting
confidence: 93%
“…Again, only questionnaires and no objective assessments had been used in this past research. Schaller et al (2016), Rudolf et al (2016) and Prince et al (2008) found similar results.…”
Section: Discussionsupporting
confidence: 61%
“…Results showed a higher pain, impairment and fatigue in patients belonging to the apprehension avoidance group compared to patients with adaptive responses and, as expected, a lower physical activity. However, despite all these conditions, the measurement of physical activity is a challenge for the treatment, rehabilitation and promotion of healthy habits in patients suffering from non-oncologic chronic pain [124,131,132].…”
Section: Accelerometry-based Activity Evaluation and Chronic Painmentioning
confidence: 99%
“…The anxiety produced by the feeling of pain causes patients to behave in a self-protective manner, avoiding the type of movement that causes the pain [11]. However, and despite all these conditions, the measurement of physical activity remains a challenge in the treatment, rehabilitation, and health promotion of patients with chronic non-oncological pain [131]. Physical activity monitoring devices have the potential to help clinicians in multiple novel pain applications, such as surgeon support tools to provide personalized post-operative care [317].…”
Section: Future Trends and Conclusionmentioning
confidence: 99%